Meta Analysis: The Effect of Using Youtube towards EFL Students’ Speaking Skill in Indonesia - Piannur Piannur; Nur Rosita (Universitas Negeri Padang, 2023)
This research aims to analyze the effect of using Youtube towards EFL students’ speaking skill for senior high school in Indonesia. The writer focuses on using meta-analysis method, in which to get a general conclusion from secondary data. By searching from Google Scholar and Sinta, fourteen data are found in the form of articles, journals and thesis. The data collected as samples are based on keywords indonesian high school students with tenth and eleventh grades as samples. The research uses JASP in order to analyze the data. Then, the findings from the analysis reveals that the effect size of using Youtube towards students’ speaking skill for grade tenth is high (RE model=1,49) and medium effect (RE model=0,64) for grade eleventh. Moreover, Youtube significantly and positively affects the students’s speaking skill for both grade tenth and eleventh.